Medicinal Plants in The Qur'an and Hadith: Lens culinaris and Vitis vinifera L.: An Article Review - Hidayat, Hakmi; Apriliana, Eva; At-Thobaniyah, Ratu Laeny; Amiruddin, Muhammad; Alfiansyah, Muhammad (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 1 (2022): Proceeding Annual Symposium on Hajj and Umrah Medicine, 2022)
There is biodiversity in various parts of the world, including fruits, which are fennel and grapes, which have multiple benefits. Fennel nuts and grapes are mentioned in several verses of the Qur'an and Hadith. This article review aims to explain the existence of fennel nuts and grapes in the Qur'an and describe the contents and benefits/applications of fennel nuts & grapes in everyday life. This article review was compiled using the literature review method from the literature found on Scopus & Google Scholar and other journal search websites related to fennel and grapes. Fennel nuts contain outstanding nutritional value because they are rich in fiber and various minerals and are relatively high in protein. Fennel also contains antinutrients (tannins and phytic acid), so it is not recommended to be consumed raw. In addition, grapes also have many benefits, such as natural antioxidants, because of their polyphenol content. At the same time, the seeds contain water, fiber, protein, minerals, and the main compound is proanthocyanidin in grape seed extract. Proanthocyanidins also have intense antioxidant activity, can activate platelets, inhibit atherosclerosis, prevent the increase of LDL, and modulate immune function.